2017
DOI: 10.3389/fpls.2016.01953
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis between Gynoecious and Monoecious Plants Identifies Regulatory Networks Controlling Sex Determination in Jatropha curcas

Abstract: Most germplasms of the biofuel plant Jatropha curcas are monoecious. A gynoecious genotype of J. curcas was found, whose male flowers are aborted at early stage of inflorescence development. To investigate the regulatory mechanism of transition from monoecious to gynoecious plants, a comparative transcriptome analysis between gynoecious and monoecious inflorescences were performed. A total of 3,749 genes differentially expressed in two developmental stages of inflorescences were identified. Among them, 32 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 80 publications
0
36
1
Order By: Relevance
“…In the present study, JcGA2ox8 was upregulated, whereas the others (JcCLA1, JcFKF1, JcDMR6, JcTT4, JcCPD, JcEBF1, JcLOX3, JcLOX2 and JcCYP79B2) were mainly downregulated (Table 3). In a previous study, the exogenous application of GA could partially prevent pistil development in gynoecious Jatropha [4]. GA2ox8 could inhibit bioactive gibberellins to reduce their content [31].…”
Section: Differential Expressed Gene Analysismentioning
confidence: 90%
See 2 more Smart Citations
“…In the present study, JcGA2ox8 was upregulated, whereas the others (JcCLA1, JcFKF1, JcDMR6, JcTT4, JcCPD, JcEBF1, JcLOX3, JcLOX2 and JcCYP79B2) were mainly downregulated (Table 3). In a previous study, the exogenous application of GA could partially prevent pistil development in gynoecious Jatropha [4]. GA2ox8 could inhibit bioactive gibberellins to reduce their content [31].…”
Section: Differential Expressed Gene Analysismentioning
confidence: 90%
“…Comparative transcriptome analysis is a better way to uncover the genetic mechanism responsible for fruit yield [3]. The genes involved in fruit yield could be identified using a comparative transcriptome analysis on contrasting materials [4]. In a previous study, 12084 ESTs have been reported in developing seeds of J. curcas [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…J. curcas JcARR6, an orthologue of the cytokinin response gene ARR6 of Arabidopsis, is significantly upregulated in female compared with male flowers at the initial stage of flower development [32]. Moreover, the expression levels of the cytokinin biosynthetic genes JcIPT5, JcCYP735A1, and JcLOG5 were higher in gynoecious J. curcas with degenerated male flowers than in monoecious J. curcas [33].…”
mentioning
confidence: 99%
“…J. curcas JcARR6, an orthologue of the cytokinin response gene ARR6 of Arabidopsis, is significantly upregulated in female compared with male flowers at the initial stage of flower development [32]. Moreover, the expression levels of the cytokinin biosynthetic genes JcIPT5, JcCYP735A1, and JcLOG5 were higher in gynoecious J. curcas with degenerated male flowers than in monoecious J. curcas [33].Because cytokinin is critical for pistil development [6,23], it is considered a major phytohormone responsible for expression of the female sex [34]. Therefore, the exogenous application of cytokinin is usually used to promote floral feminization in many plant species, such as Vitis vinifera [35], Spinacia oleracea [36], Mercurialis annua [37], Plukenetia volubilis [38], and Sapium sebiferum [39].…”
mentioning
confidence: 99%